Improving Students’ Reading Understanding Of Morphosyntax Books through Brain Mapping Based on Freedom of Learning - Caltira Rosiana; Zanuba Arifah Khofshoh (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Morphosyntax is nice material in the learning process with various activities. This study was described as Collaborative Action Research (CCAR), it proposed brain mapping based on freedom of learning as the strategy for English students to solve the students’ problems in understanding reading Morphosyntax material such as (1) lack of vocabulary mastery, (2) unrich reading subskill, (3) lack of critical reading, (4) afraid to share ideas based on what their read and background knowledge. Brain mapping toward pre-implementing, implementing, and result implementing of brain mapping could be reaching the target of the goal reading skill in morphosyntax materials with an average score of 81. Studying English with freedom of learning has a positive effect on students. Most of the students could understand what they read in morphosyntax material, so they could share their ideas, and students’ participation in the classroom was highly positive.